2017
DOI: 10.1186/s12969-017-0201-1
|View full text |Cite
|
Sign up to set email alerts
|

Short term effectiveness and experiences of a peer guided web-based self-management intervention for young adults with juvenile idiopathic arthritis

Abstract: BackgroundA web-based self-management intervention guided by peer-trainers was developed to support young adults’ self-management in coping with Juvenile Idiopathic Arthritis (JIA). To investigate its effectiveness, a randomized controlled trial (RCT) was conducted. In addition, the content of the chat and participants’ goals were studied to identify underlying processes.MethodsAn RCT with a six-month follow up period was conducted among 72 young adults with JIA, aged between 16 and 25 years old, randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 40 publications
0
35
0
1
Order By: Relevance
“…The e-mentoring interventions varied in their delivery format and involved 1 or more of the following: interactive websites [13,55-60], virtual environment [27,61-63], email [19,47,64-71], mobile apps [60,63,72], Skype video calls [60,73-75], and phone calls [68,71]. Overall, studies involving e-mentoring apps reported they were a feasible and helpful tool for facilitating students’ understanding [60,72].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The e-mentoring interventions varied in their delivery format and involved 1 or more of the following: interactive websites [13,55-60], virtual environment [27,61-63], email [19,47,64-71], mobile apps [60,63,72], Skype video calls [60,73-75], and phone calls [68,71]. Overall, studies involving e-mentoring apps reported they were a feasible and helpful tool for facilitating students’ understanding [60,72].…”
Section: Resultsmentioning
confidence: 99%
“…Studies including email-based mentorship programs reported improved mentor-mentee communication [64,65,70], particularly with respect to personal, more informal communication [19,47,70]. When compared with face-to-face mentoring, e-mentoring through interactive websites had similar outcomes for self-efficacy, quality of life, and self-management [55] and for dealing with daily life [57], but were reported to be feasible [57,60] and fun [13] while providing a safe environment for socialization [58]. Skype-based mentorship programs were feasible [73], provided flexibility [74], were informational, and provided appraisal and emotional support [75].…”
Section: Resultsmentioning
confidence: 99%
“…The Dutch developers of “Challenge your arthritis” completed the planned randomized controlled trial and published the results in 2017 [ 54 ]. A total of 72 patients with JIA were randomized into two equally sized groups.…”
Section: Discussionmentioning
confidence: 99%
“…These results differ from the outcomes of our 12-week version (ie, 1 weekly topic) of this intervention [6], where we found a significant improvement in self-determination in the experimental group compared with the controls. Although other studies on e-mentoring interventions for youth with disabilities have shown significant improvements in self-determination [20,49], very few of these studies had RCT or other rigorous designs [14]. Of the few studies that have had an RCT design, that is, Ammerlaan et al [49] explored the impact of their interactive, group-based website for youth with juvenile arthritis, they also found no significant differences between the experimental and control groups on self-efficacy, quality of life, or self-management.…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies on e-mentoring interventions for youth with disabilities have shown significant improvements in self-determination [20,49], very few of these studies had RCT or other rigorous designs [14]. Of the few studies that have had an RCT design, that is, Ammerlaan et al [49] explored the impact of their interactive, group-based website for youth with juvenile arthritis, they also found no significant differences between the experimental and control groups on self-efficacy, quality of life, or self-management. Therefore, further testing and RCTs are needed to better understand how we can best design (ie, format, length and content) an intervention for youth with physical disabilities.…”
Section: Discussionmentioning
confidence: 99%